The influence of occupational health and safety on job satisfaction of permanent employees PT. Star Rubber, Kubu Raya Regency - Fachri, Helman (Technium Business and Management, 2023)
This study aims to determine whether occupational safety and health affect the job satisfaction of permanent employees at PT. Star Rubber, Kubu Raya Regency. The population in this study are all permanent employees at PT. Star Rubber Kubu Raya Regency as many as 131 people. Determining the number of samples using the slovin formula with a sample of 98 permanent employees using random sampling technique. The analytical method used in this research is validity test, reliability test, normality test, simple linear regression analysis, correlation coefficient, coefficient of determination and model feasibility test. Based on the results of simple linear regression, the equation Y = 3.855 + 0.465X is obtained. The simple correlation coefficient results show an R value of 0.611 meaning that the relationship between occupational safety and health has a strong relationship to job satisfaction. The coefficient of determination (R2) obtained is 0.374, meaning that job satisfaction is affected by occupational safety and health by 37.4% while the remaining 62.6% is influenced by other variables not examined in this study. The results of the model feasibility test obtained a significance value of 0.000 less than 0.05 meaning that the simple linear regression model is feasible to use to predict job satisfaction which is influenced by occupational safety and health at PT. Star Rubber, Kubu Raya Regency.